Extending the institutional turn: Property, politics and development trajectories - Peter Evans (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
As institutional approaches have come to dominate the mainstream of development economics, they have outgrown earlier and simpler analyses of `property rights'. This paper focuses on the work of Acemoglu, Johnson, and Robinson, which suggests that the distribution of property rights to a `broad cross-section of the population' is the key to growth and that property rights protection that privileges elites undermines development. The paper also uses the disastrous developmental effects of AIDS in Africa to raise the issue of how institutional approaches to development will need to be modified if GDP per capita were replaced as the predominant indicator of development by broader `capability-centered' definitions. – development ; institutions ; comparative political economy
Keywords: O43; B52; P14; P51; 330; Entwicklungstheorie; Institutionalismus